Genetic variability of F2 foxtail millet population derived from ICERI-5 and Botok-10 cross - MIRA SINTIA; SINTHO WAHYUNING ARDIE; WILLY BAYUARDI SUWARNO (Society for Indonesian Biodiversity, 2023)
Abstract. Sintia M, Ardie SW, Suwarno WB. 2023. Genetic variability of F2 foxtail millet population derived from ICERI-5 and Botok-10 cross. Biodiversitas 24: 3559-3567. Foxtail millet (Setaria italica (L.) P. Beauv.) is a carbohydrate source with good tolerance to abiotic stress. High productivity, short stature, and early flowering time are the breeding targets of this species. This study aimed to obtain genetic variability of F2 foxtail millet population derived from ICERI-5 and Botok-10 crossand to predict selection response based onweighted selection index. This experiment was conducted in Bogor and consisted of 522 F2 individuals and two parental genotypes. The results showed that the F2 population had shorter plant height and earlier flowering time compared to Botok-10, and higher grainweight per plant compared to ICERI-5. Plant height, flowering time, and grainweight per plant showed moderate to high genotypic coefficient of variation with moderate to high broad-sense heritability. Weighted selection index using the three target traits resulted in ten F2 individuals with higher selection index compared to both parents, with individual number I5B10-4-96 having the highest selection index. Selection responses based on a weighted selection index indicate an expected decrease in flowering time and an increase in grain weight per plant in the next generation.